The Effect of Process Oriented Guided Inquiry Learning (POGIL) Model on Critical Thinking Skills and Collaboration Skills of Class XI Students of SMAN 14 Gowa Biology Teaching Material - Fitriah; Firdaus Daud; Alimuddin Ali (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of the POGIL learning model on critical thinking skills and collaboration skills of students in class XI sman 14 Gowa. The research design is pretest-posttest control group design. The population in the study were all grade XI students in the 2024/2025 school year which were spread into 5 study groups. The sampling technique used purposive sampling. A total of 3 study groups used in this study, namely, study group XI. B3 as an experimental class 1 applied the POGIL learning model, study group XI. B1 as experimental class 2 applied discovery learning model, and study group XI.C1 as control class applied NHT model. The data collection techniques used were critical thinking skills test and collaboration skills questionnaire. The research instruments used were a critical thinking skills test in the form of an essay of 7 questions, and a collaboration skills questionnaire of 15 statement items. The data analysis technique used was Analysis of Covariance (Ancova) using SPSS with a significant level of 0.05. Based on the Ancova test results, the significance value of the critical thinking skills variable is 0.00 <0.05 and the significance value of the collaboration skills variable is 0.00 <0.05, so it can be concluded that the application of the POGIL learning model has a significant effect or a real effect on the collaboration skills variable.